2008
DOI: 10.1111/j.1365-2982.2007.01055.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐derived growth factor signals play critical roles in differentiation of longitudinal smooth muscle cells in mouse embryonic gut

Abstract: In the development of mouse gut, longitudinal smooth muscle cells (LMC) and interstitial cells of Cajal (ICC) originate from common precursor cells expressing c-Kit. Recently, some gastrointestinal stromal tumours, which develop from smooth muscle layers of the gut and have gain-of-function mutations of c-kit, have been reported to have gain-of-function mutations of platelet-derived growth factor (PDGF) receptor alpha gene. These data raise the possibility that PDGF signalling might be involved in the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 43 publications
4
61
0
Order By: Relevance
“…The increased expression of PDGF ligands and receptor in Foxf2-deficient colons could thus be stimulating proliferation of the neonatal colonic smooth muscle and/or delaying cell cycle exit. It has been previously shown that PDGF ligands originate from the circular muscle layer and myenteric plexus of the gut, and PDGF receptor ␣ is more highly expressed in the longitudinal muscle than the circular smooth muscle layer (57). This expression pattern could explain why the circular muscle layer is less affected by Foxf2 deletion, because it lacks the receptor to respond to PDGF ligands.…”
Section: Foxf2 Is Essential For Intestinal Developmentmentioning
confidence: 79%
See 2 more Smart Citations
“…The increased expression of PDGF ligands and receptor in Foxf2-deficient colons could thus be stimulating proliferation of the neonatal colonic smooth muscle and/or delaying cell cycle exit. It has been previously shown that PDGF ligands originate from the circular muscle layer and myenteric plexus of the gut, and PDGF receptor ␣ is more highly expressed in the longitudinal muscle than the circular smooth muscle layer (57). This expression pattern could explain why the circular muscle layer is less affected by Foxf2 deletion, because it lacks the receptor to respond to PDGF ligands.…”
Section: Foxf2 Is Essential For Intestinal Developmentmentioning
confidence: 79%
“…Expansion of the myenteric plexus in Tg(smMHC-Cre-eGFP ϩ/Ϫ );Foxf2 Ϫ/Ϫ mice was confirmed by immunostaining with antibodies against the platelet-derived growth factor receptor ␣ (PDGF receptor ␣) (Fig. 4G) that is highly expressed in neurons (54 -56) and weakly expressed in smooth muscle cells (57). Consistent with increased PDGF receptor ␣ staining, qRT-PCR analysis showed increased expression of PDGF receptor ␣, as well as its ligands PDGFa and PDGFb, in Tg(smMHC-Cre-eGFP ϩ/Ϫ );Foxf2 Ϫ/Ϫ colons (Fig.…”
Section: Expansion Of the Myenteric Plexus In Tg(smmhc-cre-egfpmentioning
confidence: 99%
See 1 more Smart Citation
“…The W locus of murine chromosome 5 is the allele of the c-kit gene and several W mutations are known to be spontaneous c-kit gene mutations (Chabot et al 1988;Kitamura et al 2001). Because the c-Kit regulates ICC development by expressing an early stage of precursor cells for smooth muscle cells and ICC (Kluppel et al 1998;Kurahashi et al 2008;Torihashi et al 1997), mutant mice with W mutations show developmental deficiency of ICC in the GI tract. The W/W v mutant mice that are conventionally used as models of loss of c-Kit function have heterozygous c-kit gene mutations and a deficiency in some type of ICC, such as ICC-IM in the stomach or ICC-MY in the small intestine and distal colon (Rumessen and Vanderwinden 2003;Sanders 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Maturation of both ICCs and gut smooth muscle cells is observed at weeks 8-11, followed by the organization of muscle layers and ICC network in human embryos [25] . The expressions of c-Kit, platelet-derived growth factor, and activin are associated with the differentiation of ICCs or smooth muscle cells [26][27][28][29] . From these reports, a mechanism is suggested to the effect that activin enhances ICC/smooth muscle cell precursor cells.…”
Section: Discussionmentioning
confidence: 99%